(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
In the present study the phytochemical, barbaloin was studied for in-vitro pancreatic lipase, alpha (α)-amylase and alpha (α)-glucosidase inhibitory activities. The aim of this work is to evaluate the inhibitory activities of the phytochemical, barbaloin at different concentrations. Pancreatic lipase is an enzyme that hydrolyzes the lipids obtained from the diet which acts as an important target to treat obesity. The natural medicines that can inhibit pancreatic lipase enzyme and thus decrease absorption of dietary fat in the body gained much attention for the treatment and prevention of obesity. Diabetes mellitus is a metabolic disorder marked by an elevated level of glucose that circulates in the blood plasma. Alpha amylase and alpha glucosidase inhibitors are used to attain control over hyperglycemia in type 2 diabetes mellitus. The present study was designed to screen the novel pancreatic lipase, alpha amylase and alpha glucosidase inhibitors using a phytochemical, barbaloin in order to minimize the toxicity and side effects of the inhibitors which are used at present to treat the disorders like obesity and hyperglycemia. The phytochemical, barbaloin exhibited significant pancreatic lipase, α-amylase and α-glucosidase inhibitory activities with an IC50 value 5.52µg/ml, 8.22µg/ml and 5.81µg/ml respectively and well compared with standard orlistat for pancreatic lipase and acarbose for alpha (α)-amylase and alpha (α)-glucosidase inhibitory activities respectively.